2012
DOI: 10.1071/an11287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pistachio by-product in replacement of lucerne hay on microbial protein synthesis and fermentative parameters in the rumen of sheep

Abstract: This study was conducted to evaluate the effect of partial and total substitution of lucerne hay with pistachio by-product on nutrient intake, apparent digestibility, rumen fermentation, digesta kinetics, blood metabolites, nitrogen retention and microbial protein synthesis in Baloochi sheep. Six sheep with a bodyweight of 40.1 ± 1.77 kg fitted with ruminal and abomasal cannulae were assigned at random to three diets in a double 3 × 3 Latin-square design. The dietary treatments included a control (basal diet),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
11
15
1
Order By: Relevance
“…This is while Ghasemi et al. () reported that ruminal pH increased from 6.03 to 6.33 (p < 0.01) in Baluchi lambs as a result of including PBP by up to 50% DM of their diets. It is generally agreed that tannins reduce the rate of protein degradation in the rumen (Min et al., ; Ghasemi et al., ).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is while Ghasemi et al. () reported that ruminal pH increased from 6.03 to 6.33 (p < 0.01) in Baluchi lambs as a result of including PBP by up to 50% DM of their diets. It is generally agreed that tannins reduce the rate of protein degradation in the rumen (Min et al., ; Ghasemi et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…However, the lowest ruminal ammonia‐N concentrations measured in the current study were still above the minimum concentrations required (≥5 mg/dl) for rumen microbial growth (Satter and Roffler, ). Previous studies suggest that feeding PBP at low (≤6%) or medium (≤15%) levels had no adverse effects on rumen fermentation, digestion or performance (Ghasemi et al., ; Mokhtarpour et al., ; Shakeri et al., ). However, higher PBP levels may adversely affect voluntary feed intake and growth performance (Shakeri et al., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In one study Ghasemi et al (2012) reported that high replacement of PBP for alfalfa hay (50% of diets total DM) increased OM, CP and EE apparent digestibilities of sheep fed at requirement level. But moderated substitution of PBP (25% of diets DM) for alfalfa hay in this study did not affect digestion of nutrients.…”
Section: Animal Performancementioning
confidence: 96%